A Robust Normally Closed Pneumatic Valve for Integrated Microfluidic Flow Control - Minggan Li; Siqin Dong (Micromachines)
Accurate fluid management in microfluidic-based point-of-care testing (POCT) devices is critical. Fluids must be gated and directed in precise sequences to facilitate desired biochemical reactions and signal detection. Pneumatic valves are widely utilized for fluid gating due to their flexibility and simplicity. However, the development of reliable normally closed pneumatic valves remains challenging, despite their increasing demand in advanced POCT applications to prevent uncontrolled fluid flow. Existing normally closed valves often suffer from poor reliability and lack precise control over fluid opening pressure, due to the uncontrolled stretching of the elastomer during assembly. In this study, we propose and develop a robust method for normally closed valves. By precisely controlling the pre-stretching of the elastomer, we achieve reliable valve closure and accurate control of the opening pressure. A robust normally closed valve was designed and fabricated, and its pneumatic opening pressure was systematically studied. Experimental validations were conducted to demonstrate the reliability and effectiveness of the proposed design.